JSC OLAINFARM EFFECTS OF WASTEWATER ON THE ENVIRONMENT - Jauntirane, Anastasija; Teirumnieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Industrial wastewater differs from domestic wastewater or municipal wastewater that, is produced by industries as an undesirable by-product.Wastewater Treatment Plants belongs to chemical-pharmaceutical factory JSC Olainfarm is located in the Olaine,1km from the inhabitable area of the town. The purified water is drained into the small river Pupla, because of this is necessary good quality control and conformity Cabinet of Ministers Regulation.Wastewater treatment should environmental compliance.